Friedrich Nietzsche - Spinks, Lee (Routledge, 2003)
It is difficult to imagine a world without common sense, the distinction between truth and falsehood, the belief in some form of morality or an agreement that we are all human. But Friedrich Nietzsche did imagine such a world, and his work has become a crucial point of departure for contemporary critical theory and debate. This volume introduces this key thinker to students of literary and cultural studies, offering a lucid account of Nietzsche's thought on: * anti-humanism * good and evil * the Overman * nihilism * the Will to Power. Lee Spinks prepares readers for their first encounter with Nietzsche's most influential texts, enabling them to begin to apply his thought in studies of literature, art and contemporary culture.